Pseudohypoparathyroidism type 1A presenting as short stature and congenital hypothyroidism - Ragini Kondetimmanahalli; Jane Lynch; Gary Francis; Heather Gardner; Radhika Pillai (Endocrinology, Diabetes & Metabolism Case Reports)
Short stature is a common complaint among pediatric visits and the differential diagnosis is extensive. Although some variations in growth are normal, deviation from normal growth is often the first symptom of chronic disease in children. This is true for hormone abnormalities including growth hormone deficiency, hypothyroidism and glucocorticoid excess. However, reduced growth velocity can also occur as the first sign of chronic anemia, malnutrition, deprivation (psychosocial dwarfism), chromosomal abnormalities, genetic syndromes and inflammatory bowel diseases. For the primary care provider, simple measures of standing height, sitting height, arm span, weight, body mass index (BMI) and bone age (BA) will lead to the correct diagnosis in most short children. Screening laboratory studies for endocrine disorders, a skeletal survey if skeletal disproportion is evident, a karyotype or microarray (microarray favored if developmental delay is also present) and genetic testing for monogenic disorders will lead to a specific diagnosis in an additional subset of short children. This case presented a diagnostic dilemma that spanned all these possibilities and served as a focal point for the review of normal growth and growth abnormalities.